EFFECT OF ACQUISITION ON IMPROVING COMPANY PERFORMANCE - Đaković, Miloš; Inđić, Milica (Economic Outlook, 2022)
Today, external factors are increasingly influencing companies and financial management. Intense competition among corporations, technological change, fluctuations in inflation and interest rates, global economic uncertainty, fluctuating exchange rates, changes in tax laws and ethical concerns about certain financial affairs, are everyday phenomena that need to be addressed. It is this previously mentioned intense competition between companies that leads to various forms of financial restructuring. One of the most common types of financial restructuring is an acqusition, which will be the subject of this paper. There are different types of corporate restructuring of the company, which include, organizational, financial, ownership, etc. And as already mentioned, one of the main organizational types of restructuring is acquisition. The aim of this paper is to see the effect of аcquisition on the company's business through the basic ratio analysis of indicators before and after the acquisition of companies and to see the synergetic effect of the acquisition and projected expected future financial results of the company.
Keywords: Financial restructuring; acquisition; ratio analysis; synergetic effect